Practical Ruby Gems - Berube, David (Apress, 2012)
Specifically, RubyGems is a package-management system for Ruby applications and libraries. It lets you install Ruby code—called gems—to any computer running Ruby. It can resolve dependences for you, so if you want to install a given piece of software, RubyGems can handle that for you. It can even resolve version dependencies—so that if a certain gem or your code requires a certain version of another gem, it can take care of that. It also wraps all of this functionality in a very easy-to-use package.